Climate change, financial development and economic performance of the agricultural sector in Nigeria (International Journal of Sustainable Development & World Policy, 2026)
The study investigated the impact of climate change and financial development on the economic performance of Nigeria's agricultural sector. It highlighted the severe threat posed by climate change, primarily through greenhouse gas emissions (GHG), and the influence of financial development dynamics on agricultural productivity in developing countries. An ex-post-facto research design was employed, utilizing data from 1990 to 2023 sourced from the World Development Indicators and the Central Bank of Nigeria. The independent variables included greenhouse gas emissions carbon dioxide (CO2), methane (CH4), and nitrous oxide (N2O). Financial development variables encompassed inflation, exchange rate, and gross capital formation, while the dependent variable was agricultural value added. The Fully Modified Ordinary Least Squares (FMOLS) method was used as the analytical tool, along with other diagnostic tools. The findings indicated a significant negative relationship between carbon dioxide emissions (CO2) and agricultural value added. Methane emissions (CH4) showed no significant impact, whereas nitrous oxide (N2O) positively affected productivity. These results underscore the complex dynamics between greenhouse gases, financial development, and agricultural productivity. The study emphasizes the need for targeted policies to mitigate GHG emissions by promoting sustainable agricultural practices to ensure long-term food security and resilience in Nigeria. The implications of financial development indicators—such as inflation, exchange rates, and gross capital formation—in climate change studies suggest that improving access to financial resources could facilitate investments in sustainable agriculture. Policymakers should consider enhancing financial infrastructure to support farmers in adopting environmentally friendly practices.